Online Learning in Bangladesh during COVID-19: Perceived Effectiveness, Challenges, and Suggestions - Md. Saidur Rahaman; Iqbal Hossain Moral; Md. Mizanur Rahman; Mohammad Sahabuddin; Adedeji Babatunji Samuel (Camarines Sur Polytechnic Colleges, 2021)
The primary purpose of this research is to highlight the effectiveness and challenges of Online Learning (OL) for Bangladesh during COVID-19. Besides, the researchers have proposed some suggestions based on the findings of this research to overcome from those challenges. Fifteen students using purposive sampling from Bangladesh's private, public, and national universities have taken as a study sample. Researchers generated headings which will be asked to the respondents in relation to the research questions through the secondary sources (published articles, journals, reports, conference proceedings, newspapers, and government records). After that, data triangulation has been validated by the semi-structured interview of 15 students. According to the findings, online learning is now somehow effective; but, it faces several challenges in Bangladesh's educational system. The students, guardians, university authorities such as University Grant Commission (UGC) and the Ministry of Education will be benefited from these findings.  The study only looked at Bangladeshi students' viewpoints, which may or may not be similar to those of other countries. As a result, generalization of the findings is less possible; consequently, more students from other countries should be included in the future.